Computer security--ESORICS 2011 16th European symposium on research in computer security, Leuven, Belgium, September 12-14,2011. proceedings - European symposium on research in computer security 2011 Leuven, Belgium); Atluri, Vijay; Diaz, Claudia; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the 16th European Symposium on Computer Security, ESORICS 2011, held in Leuven, Belgium, in September 2011. The 36 papers included in the book were carefully reviewed and selected from 155 papers. The articles are organized in topical sections on wireless security; Web security; forensics, biometrics and software protection; access control; cryptography and protocol analysis; information flow, side channels, and vulnerability analysis; usability, trust, and economics of security and privacy; and privacy.
Electronic reproduction.
Keywords: Computer security -- Congresses; Electronic books